An introduction to the social and political philosophy of Bertolt Brecht : revolution and aesthetics - Squiers, Anthony (Consciousness, literature & the arts, 2014)
Bertolt Brecht is widely considered one of the most important figures in Twentieth Century literature. While there is a broad corpus of scholarship which analyzes the formalistic elements of Brecht's work, much of this has been limited by formalistic approaches and has neglected his unique contributions to Marxist philosophy. This book serves to remedy this by reconstructing Brecht's social and political philosophy into a single theoretical framework for the first time. It presents Brecht's thought in context of a revolutionary Marxist aesthetic and explores his vision of consciousness as it relates to historical materialism, the dialectic of enlightenment, social ontology, epistemology and ethics. This is accomplished by meticulous readings of his theoretical writings and close analysis of three important plays, The Good Woman of Setzuan, Life of Galileo, and his adaption of Coriolanus . In doing so, this book reveals Brecht's relevance today for anyone interested in politics and aesthetics.